Influence of the Chemical Structure of Perylene Derivatives on the Performance of Honey-Gated Organic Field-Effect Transistors (HGOFETs) and Their Application in UV Light Detection - Fernandes Dias, Jose Diego [UNESP]; Vieira, Douglas Henrique [UNESP]; Serghiou, Theodoros; Rivas, Carlos J.; Constantino, Carlos J. L. [UNESP]; Jimenez, Liliana B.; Alves, Neri [UNESP]; Kettle, Jeff (American Chemical Society (ACS), 2024)
Electronics based on natural or degradable materials are a key requirement for next-generation devices, where sustainability, biodegradability, and resource efficiency are essential. In this context, optimizing the molecular chemical structure of organic semiconductor compounds (OSCs) used as active layers is crucial for enhancing the efficiency of these devices, making them competitive with conventional electronics. In this work, honey-gated organic field-effect transistors (HGOFETs) were fabricated using four different perylene derivative films as OSCs, and the impact of the chemical structure of these perylene derivatives on the performance of HGOFETs was investigated. HGOFETs were fabricated using naturally occurring or low-impact materials in an effort to produce sustainable systems that degrade into benign end products at the end of their life. It is shown that the second chain of four carbons at the imide position present in perylenes N,N′-bis(5-nonyl)-perylene-3,4,9,10-bis(dicarboximide) (PDI) and N,N′-bis(5-nonyl)-1-naphthoxyperylene-3,4,9,10-bis(dicarboximide) (PDI-ONaph) reduces π-stacking interaction in the active layer, leading to lower AC conductivity and the non-functionality of HGOFETs. On the other side, the chain-on molecular orientation in the film of N,N′-dibutylperylen-3,4:9,10-bis(dicarboximide) (BuPTCD) was fundamental for the efficiency of HGOFETs, showing a better performance than the HGOFETs of N,N′-bis(2-phenylethyl)-3,4:9,10-bis(dicarboximide) (PhPTCD), which has a face-on molecular orientation. Finally, the HGOFETs of BuPTCD and PhPTCD are good candidates as UV light detectors and are used for the detection of UV radiation.
Keywords: chemical structure; HGOFETs; perylenes; sustainability; UV light detector